1985
DOI: 10.1111/j.1471-0528.1985.tb03019.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus type 16 DNA sequences in cervical intraepithelial neoplasia and invasive carcinoma of the cervix

Abstract: The frequency of human papillomavirus (I-IPV) type 16 in premalignant and malignant lesions of the cervix was investigated and compared with the detection of HPV type 6. In cervical intraepithelial neoplasia (CIN) grades 1-111 HPV bwas detcctcd in 28% and HPV 16 in 62Y0 of patients whereas 90% of malignant lesions contained HPV 16 only. In the CIN lesions there was an increase in HPV 16 detection as the severity of disease increased while the levcl of detection of HPV 6 decreased. Only three (18%) of the cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(58 citation statements)
references
References 11 publications
4
53
0
1
Order By: Relevance
“…Similar prevalence was shown for HPV type 16 and 18 in dysplastic lesions by other authors (van Den Brule et al, 1991;Cornelissen et al, 1992;Cuzick et al, 1994;Holowaty et al, 1999;Voglino et al, 2000). Observation of a higher frequency of HR-HPV types in women with severe dysplastic lesions and CIS than in mild dysplsia is also in agreement with earlier reports (McCance et al, 1985;Cornelissen et al, 1992;Cuzick et al, 1994;Delvenne et al 1994). Gradual increase in the frequency of high risk HPV types 16 and 18 from mild to moderate to severe dysplastic lesions to invasive cervical cancer suggests that the frequency of high risk HR-HPV infection changes as a function of severity of cervical lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Similar prevalence was shown for HPV type 16 and 18 in dysplastic lesions by other authors (van Den Brule et al, 1991;Cornelissen et al, 1992;Cuzick et al, 1994;Holowaty et al, 1999;Voglino et al, 2000). Observation of a higher frequency of HR-HPV types in women with severe dysplastic lesions and CIS than in mild dysplsia is also in agreement with earlier reports (McCance et al, 1985;Cornelissen et al, 1992;Cuzick et al, 1994;Delvenne et al 1994). Gradual increase in the frequency of high risk HPV types 16 and 18 from mild to moderate to severe dysplastic lesions to invasive cervical cancer suggests that the frequency of high risk HR-HPV infection changes as a function of severity of cervical lesions.…”
Section: Discussionsupporting
confidence: 92%
“…However, in studies of CIN, the definition of a case is generally based on cytological and histological criteria, and it can be difficult to distinguish, on morphological grounds only, CIN from the subclinical HPV infection sometimes referred to as 'flat and atypical condylomas' (Koss, 1987). A number of studies have reported high rates of reclassification from CINI to HPV infection using recently developed cytological criteria, which may also reflect a high prevalence of mixed CIN/HPV lesions (Meisels et al, 1982(Meisels et al, , 1983 (Crum et al, 1986;Schneider et al, 1987;Wagner et al, 1984 (Meanwell et al, 1987), and only two others even mention the mean age of cases and controls (McCance et al, 1985;Toon et al, 1986).…”
Section: Definition Of Cases and Controlsmentioning
confidence: 99%
“…The table gives the number of subjects tested in each cervical lesion group (invasive carcinoma, cervical intraepithelial neoplasia, referred to as CIN, or normal), and the percentage positive for various types of HPV in each group. In five of these studies, HPV prevalence rates are given separately for the three degrees of CIN (Lorincz et al, 1986;McCance et al, 1985;Schneider et al, 1985;Schneider et al, 1987;Wagner et al, 1984). The initial impression is that within each study women with cervical neoplasia have HPV DNA of types 16 and 18 detectable in their cervical cells more frequently than women with normal cervices, that the prevalence rates increase with the severity of the lesion, and that there is a considerable variation in prevalence within each lesion group, although most of the studies are based on small numbers and different hybridisation techniques have been used.…”
mentioning
confidence: 99%
“…These observations all point to the existence of a venereally transmitted causative agent (Beral, 1974) and there is now much evidence to indicate that certain types of the human papilloma virus (HPV) have a central role in this process. HPV DNA has been found in invasive cancers (Durst et al, 1983;zur Hausen, 1984;McCance et al, 1985;Grubb, 1986), pre-invasive lesions (Walker et al, 1984;Campion et al, 1985;De Villiers et al, 1987) and has been found to be related to progression of disease (Campion et al, 1986). Promiscuity in men has also been linked to increased risk in their sexual partners (Buckley et al, 1981;Zunzunegui et al, 1986) and recent studies have shown that males harbour human papilloma virus in penile lesions Villa & Lopes, 1986) and that sexual partners share increased risk of genital cancer (Kessler, 1976;Smith et al, 1980;Barrasso et al, 1987).…”
mentioning
confidence: 99%